Image forming method and image forming apparatus

JP2025042350APending Publication Date: 2025-03-27KONICA MINOLTA INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023149305
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-03-27

Smart Images

  • Figure 2025042350000001_ABST
    Figure 2025042350000001_ABST
Patent Text Reader

Abstract

To provide an image forming method that can form an image excellent in low temperature fixability and having less roughness on a surface of an image.SOLUTION: An image forming method includes the steps of: forming, on a recording medium, a toner image including a white toner image and a colored toner image arranged on the white toner image; and fixing the toner image onto the recording medium. In the fixing step, the recording medium on which the toner image is formed is nipped between an annular belt that is supported, at least partially on its inner periphery, by a heating member and an opposite member that is opposite to the heating member with the annular belt therebetween, and the toner image is fixed onto the recording medium. The white toner and the colored toner satisfy the following relationship. 0.3≤logμ(W110)-logμ(C100).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an image forming method and an image forming apparatus. [Background technology]

[0002] Conventionally, in electrophotographic image formation, full-color images are formed using four colors, yellow, magenta, cyan, and black. When a full-color image is formed on a white recording medium, it is easy to obtain an image with good color development, but when the full-color image is formed on a recording medium such as colored paper, black paper, or transparent film, it is difficult to obtain an image with good color development. Therefore, it has been proposed to use a white toner as a fifth color toner as a base toner to form a white background image (for example, see Patent Document 1).

[0003] In addition, there is a demand for a toner image transferred onto a recording medium to be fixed at a low temperature (low-temperature fixability). In response to this demand, a method has been proposed for fixing a toner image onto the recording medium using a fixing device having a circular belt, a heating member disposed on the inner peripheral side of the circular belt, and an opposing member disposed on the outer peripheral side of the circular belt so as to face the heating member (see, for example, Patent Document 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2022-48310 [Patent Document 2] Patent Publication No. 2021-162839 Summary of the Invention [Problem to be solved by the invention]

[0005] In the fixing device as described above, the recording medium S on which the toner layer T (toner image) is formed is heated in a nipped state between the fixing belt 61 (annular belt) whose inner circumferential surface is partially supported by the heater 62 (heating member) and the pressure roller 63 (opposing member) opposed via the heater 62 and the fixing belt 61 (see FIG. 1A described later). Therefore, the heat of the heater 62 is easily transferred directly to the toner layer T, and the toner image is easily fixed on the recording medium even at a relatively low temperature.

[0006] However, when a toner layer formed by overlapping white toner and color toner on a recording medium is fixed using the fixing device, the fixing belt is likely to receive a large frictional force when rubbing against the toner layer, which may cause the fixing belt to wear and roughen the surface of the image. In addition, the tension balance on the fixing belt may be lost due to the wear of the fixing belt, which may lead to the breakage of the fixing belt.

[0007] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an image forming method and an image forming apparatus capable of forming an image having excellent low-temperature fixing property and less surface roughness. [Means for solving the problem]

[0008] [1] An image forming method comprising the steps of: forming a toner image on a recording medium, the toner image including a white toner image and a color toner image disposed on the white toner image; and fixing the toner image onto the recording medium, wherein in the fixing step, the recording medium on which the toner image has been formed is nipped between a circular belt, at least a portion of whose inner circumference is supported by a heating member, and an opposing member that faces the heating member and the circular belt via the circular belt, to fix the toner image onto the recording medium under heat, and wherein the white toner constituting the white toner image and the color toners constituting the color toner image satisfy the following formula: 0.3≦lоgμ(W110)-lоgμ(C100) (logμ(W110) is the logarithm of the viscosity of the white toner at 110° C., logμ(C100) is the logarithm of the viscosity of the color toner at 100°C. [2] The image forming method according to [1], wherein in the fixing step, the toner image is heated at 130° C. or higher and 170° C. or lower. [3] The image forming method according to [1] or [2], wherein log μ(W110) is 3.9 or more and 5.5 or less. [4] The image forming method according to any one of [1] to [3], wherein the white toner and the color toner satisfy the following formula: 0.5≦lоgμ(W110)-lоgμ(C100)≦1.5 [5] The image forming method according to any one of [1] to [4], wherein the white toner contains white toner base particles, and the white toner base particles have an average circularity of 0.920 or more and 0.955 or less. [6] The image forming method according to any one of [1] to [5], wherein the color toner contains color toner base particles, and the average circularity of the color toner base particles is 0.920 or more and 0.955 or less. [7] The image forming method according to any one of [1] to [6], wherein the water content of the white toner and the water content of the color toners are each 0.1% or more and 0.6% or less. [8] An image forming apparatus having a fixing unit that fixes a toner image, including a white toner image and a color toner image disposed on the white toner image, onto a recording medium, the fixing unit having a circular belt, a heating member disposed on the inner surface of the circular belt, and an opposing member disposed on the outer surface of the circular belt opposite the heating member via the circular belt, the fixing unit nips the recording medium on which the toner image has been formed between the circular belt supported by the heating member and the opposing member, and fixes the toner image to the recording medium, and the white toner and the color toner satisfy the following formula: 0.3≦lоgμ(W110)-lоgμ(C100) (logμ(W110) is the logarithm of the viscosity of the white toner at 110° C., logμ(C100) is the logarithm of the viscosity of the color toner at 100°C. Effect of the Invention

[0009] According to the present invention, it is possible to provide an image forming method and an image forming apparatus capable of forming an image having excellent low-temperature fixing property and having little surface roughness. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1A is a schematic diagram showing how a toner image is fixed on a recording medium under conventional conditions, and FIG. 1B is a schematic diagram showing how a toner image is fixed on a recording medium under conditions according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing a configuration of an image forming apparatus according to an embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic enlarged cross-sectional view showing a main part of the fixing unit in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] As described above, when a toner layer in which white toner and color toner are superimposed is fixed onto a recording medium using the fixing device, the fixing belt is likely to wear out or break. The mechanism behind this is believed to be as follows.

[0012] FIG. 1A is a schematic diagram showing how a toner image is fixed under conventional conditions, and FIG. 1B is a schematic diagram showing how a toner image is fixed under conditions according to an embodiment of the present invention.

[0013] When white toner WT and color toner CT are superimposed to form an image, the amount of toner adhering to the recording medium S increases. If the entire toner layer T with a large amount of adhesion is melted as in the conventional method, the toner layer T melts well as a whole and is likely to be firmly fused to the recording medium (see FIG. 1A). Therefore, the sliding fixing belt 61 is likely to be subjected to a large frictional force when it separates from the toner layer T firmly fused to the recording medium, which makes the fixing belt 61 prone to wear and breakage.

[0014] In particular, the fixing belt 61 is easily damaged because it is easily subjected to heat directly from the heater 62. In addition, the heater 62 has a pad shape and a relatively large area, so the area on which the fixing belt 61 is subjected to frictional force is also large. Therefore, the fixing belt 61 is more likely to wear out or break.

[0015] In response to this, the inventors have discovered that by not melting a portion of the toner layer T, rather than melting the entire toner layer T, it is possible to reduce the frictional force that the fixing belt 61 receives from the surface of the toner layer T (see FIG. 1B).

[0016] That is, in the image forming method according to one embodiment of the present invention, the viscosity of the white toner WT in the lower layer is made higher than the viscosity of the color toner CT in the upper layer by a predetermined value or more near the fixing temperature. Specifically, the logarithm value log(W110) of the viscosity of the white toner near the fixing temperature (100 to 110° C.) is made higher than the logarithm value logC(100) of the viscosity of the color toner by 0.3 or more. The fixing temperature refers to the set temperature (heater temperature) of the fixing belt in contact with the toner layer T, and in the fixing unit 60 in FIG. 3 described later, it means the temperature of the heater 62.

[0017] As a result, the color toner CT in the upper layer melts, while the white toner WT in the lower layer does not melt completely and tends to remain in particulate form (see FIG. 1B). In other words, the surface of the toner layer T melts and becomes less viscous, while the inside of the toner layer T does not melt completely, and some gaps are maintained between the particles. This makes it easier for the frictional force generated in the nip to be dispersed to the contact areas between the toner base particles. As a result, the frictional force generated between the surface of the toner layer T and the surface of the fixing belt 61 is reduced, which is thought to suppress roughening of the image surface and breakage of the fixing belt 61.

[0018] In addition, it is preferable that the average circularity of the toner base particles contained in these toners is appropriately low, because if the average circularity of the toner base particles is appropriately low, appropriate gaps are easily formed between the toner base particles, and the frictional force that the sliding fixing belt receives from the toner layer T is easily dispersed and further reduced.

[0019] An image forming method according to an embodiment of the present invention will now be described in detail. First, the toner will be described, and then the image forming method will be described.

[0020] 1. Toner The toner used in the image forming method according to the present embodiment is a developer for developing an electrostatic image (electrostatic latent image) formed on an image carrier such as a photoconductor. In the present embodiment, a white toner and a color toner are used.

[0021] The relationship between the viscosities of the white toner and the color toners is adjusted to satisfy the following formula (1). Formula (1): 0.3≦lоgμ(W110)-lоgμ(C100) (logμ(W110) is the logarithm of the viscosity of the white toner at 110°C, logμ(C100) is the logarithm of the viscosity of the color toner at 100°C.

[0022] When logμ(W110)-logμ(C100) is 0.3 or more, the viscosity of the white toner in the lower layer is moderately higher than that of the color toner in the upper layer near the fixing temperature. That is, the surface of the toner image becomes less viscous and melts, while the inside of the toner image does not melt completely, and some gaps are maintained between the particles. This can reduce the friction force that the fixing belt receives at the nip portion. From the same viewpoint, logμ(W110)-logμ(C100) is preferably 0.5 or more. The upper limit of logμ(W110)-logμ(C100) is not particularly limited, but from the viewpoint of not impairing low-temperature fixing property, it is preferably 2.0 or less, and more preferably 1.5 or less.

[0023] The viscosity of the toner can be measured using a flow tester (for example, CFT-500 manufactured by Shimadzu Corporation) under the following conditions and procedures. 1) First, 1.1 g of toner in powder form is placed in a cylinder kept at 50°C and preheated for 300 seconds. 2) Next, while heating at a rate of 6°C / min, the toner is pressurized with a plunger (applied with a load of 2 kg) to cause the molten toner to flow out from a cylindrical die hole (hole inner diameter: 1.0 mm, die length: 1.0 mm) provided at the bottom of the cylinder. 3) Measure the data until dissolution is completely completed. Then, read the viscosity value when it reaches 110°C for white toner, and when it reaches 100°C for colored toner, then convert them into logarithms to calculate logμ(W110) and logμ(C100).

[0024] The above-mentioned viscosity relationship can be adjusted by adjusting the resin composition of the white toner and the color toner. For example, if the melting point of the binder resin contained in the white toner is made higher than the melting point of the binder resin contained in the color toner, the difference in the logarithmic values ​​is likely to become large.

[0025] The viscosity of the white toner may be within a range that satisfies the above formula (1), but from the viewpoint of further reducing the frictional force received by the fixing belt, it is preferable that the viscosity is moderately high. Specifically, the logμ(W110) of the white toner is preferably 3.9 or more and 5.5 or less. When the logμ(W110) is 3.9 or more, the ratio of the white toner particles that remain unmelted even when heated during fixing can be increased moderately. As a result, the entire toner on the recording medium does not fuse too much, and the frictional force received by the fixing belt can be further dispersed. On the other hand, when the logμ(W110) is 5.5 or less, the ratio of the white toner particles that do not melt does not become too large, so that the toner is less likely to be separated into a molten color toner layer and a powdery white toner layer. As a result, it is possible to further suppress the upper color toner layer from being peeled off by the fixing belt and the color shift of the image after fixing. In addition, the fixability to the recording medium is less likely to be impaired. From the same viewpoint, the logμ(W110) is more preferably equal to or greater than 4.1 and equal to or less than 5.2.

[0026] The viscosity of the color toner may be within a range that satisfies the above formula (1), but from the viewpoint of maintaining low-temperature fixability, it is preferable that the viscosity is moderately low. For example, the logμ(C100) of the color toner is preferably 3.5 or more and 4.5 or less. When the logμ(C100) is 3.5 or more, the surface layer of the toner layer does not melt too much due to heating during fixing, so that the frictional force received by the fixing belt can be further reduced. On the other hand, when the logμ(C100) is 4.5 or less, the color toner can be melted more by heating during fixing, so that the fixability of the toner layer to the recording medium can be further improved. From the same viewpoint, the logμ(C100) is more preferably 3.9 or more and 4.3 or less.

[0027] The viscosity of each toner can be adjusted mainly by the amount and composition of the binder resin contained in the toner. For example, increasing the amount of binder resin contained in the toner or decreasing the content ratio of crystalline resin to amorphous resin tends to increase the viscosity of the white toner.

[0028] Each toner will be described in detail below.

[0029] 1-1. White toner The white toner contains white toner particles. The white toner particles contain white toner base particles and may further contain an external additive, if necessary.

[0030] 1-1-1. White toner base particles The white toner base particles contain a binder resin and a white colorant.

[0031] (Binding resin) The binder resin binds the toner to the recording medium. The binder resin may contain an amorphous resin, may contain a crystalline resin, or may contain both a crystalline resin and an amorphous resin. The binder resin may be of only one type, or may contain two or more types.

[0032] In this embodiment, from the viewpoint of achieving both image strength and low-temperature fixability, the binder resin preferably contains an amorphous resin and a crystalline resin.

[0033] In this specification, the term "crystalline resin" refers to a resin whose melting point is observed in a measurement by differential scanning calorimetry (DSC). In addition, the term "amorphous resin" refers to a resin whose melting point is not observed in a measurement by DSC. In addition, in this specification, the term "a resin whose melting point is observed" refers to a resin whose melting point is not a stepwise endothermic change but a clear endothermic peak in DSC, specifically, a peak whose half-width of the endothermic peak is within 15°C is observed when measured at a heating rate of 10°C / min.

[0034] In addition, in this specification, the expression "the binder resin contains an amorphous resin" means that the binder resin may contain an amorphous resin itself, or may be contained as a segment contained in another resin, such as an amorphous resin segment in a hybrid resin. Similarly, "the binder resin contains a crystalline resin" may mean an embodiment in which the binder resin contains the crystalline resin itself, or the crystalline resin may be contained as a segment contained in another resin, such as a crystalline polyester polymer segment in a hybrid resin.

[0035] (amorphous resin) Examples of the amorphous resin include styrene resin, vinyl resin (acrylic resin, styrene-acrylic resin, etc.), urethane resin, urea resin, polyester resin, silicone resin, olefin resin, polyamide resin, etc. Only one type of these may be included, or two or more types may be included. Among them, it is preferable that the binder resin includes an amorphous polyester resin. This is because it has good compatibility with the crystalline polyester resin described later.

[0036] The amorphous polyester resin contains a polycondensation unit of a divalent or higher carboxylic acid (polycarboxylic acid) and a divalent or higher alcohol (polyhydric alcohol).

[0037] Examples of polycarboxylic acids include saturated aliphatic dicarboxylic acids such as succinic acid, sebacic acid, and dodecanedioic acid; unsaturated aliphatic dicarboxylic acids such as maleic acid, fumaric acid, and itaconic acid; alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid; aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, and terephthalic acid; trivalent or higher polycarboxylic acids such as trimellitic acid and pyromellitic acid; acid anhydrides thereof; and alkyl esters having 1 to 3 carbon atoms thereof. These may be used alone or in combination of two or more. Among them, from the viewpoint of increasing the viscosity of the white toner, the polycarboxylic acid of the amorphous polyester resin in the white toner base particles preferably contains an aromatic dicarboxylic acid, and more preferably contains terephthalic acid.

[0038] Examples of polyhydric alcohols include aliphatic diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, neopentyl glycol, and 1,4-butenediol; and trihydric or higher alcohols such as glycerin, pentaerythritol, trimethylolpropane, and sorbitol. The polyhydric alcohol is preferably an aliphatic diol.

[0039] As the polyvalent carboxylic acid and polyhydric alcohol, in addition to the above-mentioned materials, for example, bisphenols such as bisphenol A and bisphenol F, and alkylene oxide adducts of bisphenols such as their ethylene oxide adducts and propylene oxide adducts can be used. These can be used alone or in combination of two or more. Among them, it is preferable that the polyhydric alcohol contains an ethylene oxide adduct or a propylene oxide adduct of bisphenol A.

[0040] The number average molecular weight of the amorphous polyester resin is not particularly limited, but is preferably, for example, from 2000 to 10000. The number average molecular weight can be measured in terms of polystyrene by gel permeation chromatography.

[0041] The content of the amorphous resin is, for example, preferably 50% by mass or more and 99% by mass or less, more preferably 55% by mass or more and 83% by mass or less, and more preferably 60% by mass or more and 80% by mass or less, based on the resin (binder resin) constituting the toner base particles.

[0042] [Crystalline resin] Examples of the crystalline resin include crystalline polyester resin, crystalline polyamide resin, crystalline polyurethane resin, crystalline polyacetal resin, crystalline polyphenylene sulfide resin, and crystalline polyether ether ketone resin. These may be included in one type or in two or more types. Among them, the crystalline resin preferably contains a crystalline polyester resin. This is because the crystalline polyester resin melts during heat fixing and easily acts as a plasticizer for the amorphous resin, and is more likely to improve low-temperature fixing properties.

[0043] The crystalline polyester resin contains a polycondensation unit of a polycarboxylic acid and a polyhydric alcohol. The polycarboxylic acid and the polyhydric alcohol constituting the crystalline polyester resin may be the same as the polycarboxylic acid and the polyhydric alcohol constituting the amorphous polyester resin described above.

[0044] In particular, from the viewpoint of further enhancing low-temperature fixability while satisfying the relationship of the above formula (1), the polyvalent carboxylic acid of the crystalline polyester resin contained in the white toner base particles preferably contains an aliphatic dicarboxylic acid, and more preferably contains a linear aliphatic dicarboxylic acid.

[0045] The monomers constituting the crystalline polyester resin preferably contain 50% by mass or more, and more preferably 80% by mass or more, of linear aliphatic monomers. By making the linear aliphatic monomer 50% by mass or more, it becomes easier to maintain crystallinity in the toner, and by making it 80% by mass or more, it becomes possible to maintain more sufficient crystallinity.

[0046] The melting point of the crystalline polyester is, for example, preferably from 50° C. to 85° C., and more preferably from 60° C. to 80° C. When the melting point of the crystalline polyester is within the above range, the toner base particles can be more easily softened, and the low-temperature fixability of the toner can be further improved.

[0047] The number average molecular weight (Mn) of the crystalline polyester is preferably from 2000 to 10000. When the number average molecular weight (Mn) of the crystalline polyester is within the above range, the low temperature fixability becomes better.

[0048] The content of the crystalline resin is preferably 1% by mass or more and 50% by mass or less, more preferably 17% by mass or more and 45% by mass or less, and even more preferably 20% by mass or more and 40% by mass or less, based on the binder resin. When the content of the crystalline resin is 1% by mass or more, the low-temperature fixing property of the toner can be further improved. When the content of the crystalline resin is 50% by mass or less, the heat resistance and strength of the toner are less likely to be impaired.

[0049] In particular, the content ratio of the amorphous polyester resin to the crystalline polyester resin is preferably 83 / 17 to 55 / 45 (mass ratio), and more preferably 80 / 20 to 60 / 40 (mass ratio). When the content ratio of the amorphous polyester resin is high, the melting point of the binder resin tends to be high, and therefore the viscosity of the white toner tends to be high. When the content ratio of the amorphous polyester resin is low, the content ratio of the crystalline polyester resin tends to be high, and therefore the viscosity of the white toner tends to be low.

[0050] The total amount of the amorphous polyester resin and the crystalline polyester resin is preferably 10% by mass or more, and more preferably 15% by mass or more and 100% by mass or less, based on the binder resin.

[0051] As described above, the crystalline resin and the amorphous resin may be included as a hybrid resin including a crystalline resin segment and an amorphous resin segment. The toner base particles including such a hybrid resin may have a core-shell structure. It is preferable that the core in the core-shell structure includes a crystalline resin and the shell includes an amorphous resin.

[0052] The binder resin content in the white toner base particles is preferably 20% by mass or more and 99% by mass or less, more preferably 30% by mass or more and 95% by mass or less, and even more preferably 40% by mass or more and 90% by mass or less, based on the weight of the white toner base particles. When the binder resin content is 20% by mass or more, the strength of the formed image can be further increased.

[0053] (white colorant) Examples of white colorants include inorganic pigments (e.g., heavy calcium carbonate, light calcium carbonate, titanium oxide, aluminum hydroxide, titanium white, talc, calcium sulfate, barium sulfate, zinc oxide, magnesium oxide, magnesium carbonate, amorphous silica, colloidal silica, white carbon, kaolin, calcined kaolin, delaminated kaolin, aluminosilicate, sericite, bentonite, smexite, etc.), and organic pigments (e.g., polystyrene resin particles, urea formalin resin particles, etc.). From the viewpoint of electrostatic chargeability and hiding power, the white colorant is preferably titanium oxide. Titanium oxide may have any crystal structure, such as anatase type, rutile type, or brookite type.

[0054] The content of the white colorant is preferably 30 parts by mass or more and 75 parts by mass or less, and more preferably 40 parts by mass or more and 60 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0055] (Other ingredients) The white toner base particles may further contain other components such as a release agent and a charge control agent, if necessary.

[0056] As the release agent, various known waxes can be used. Examples of waxes include polyolefin waxes such as polyethylene wax and polypropylene wax, branched chain hydrocarbon waxes such as microcrystalline wax, long chain hydrocarbon waxes such as paraffin wax and sazol wax, dialkyl ketone waxes such as distearyl ketone, carnauba wax, montan wax, behenic acid behenate, trimethylolpropane tribehenate, pentaerythritol tetrabehenate, pentaerythritol diacetate dibehenate, glycerin tribehenate, 1,18-octadecanediol distearate, trimellitic acid tristearyl, distearyl maleate, and other ester waxes, and amide waxes such as ethylenediamine behenylamide and trimellitic acid tristearylamide. These release agents may be used alone or in combination of two or more.

[0057] The content of the release agent is not particularly limited, but is preferably from 4 to 30 parts by mass, and more preferably from 5 to 20 parts by mass, relative to 100 parts by mass of the binder resin.

[0058] The charge control agent can adjust the chargeability of the toner base particles. Examples of the charge control agent include nigrosine dyes, metal salts of naphthenic acid or higher fatty acids, alkoxylated amines, quaternary ammonium salt compounds, azo metal complexes, salicylic acid metal salts or metal complexes thereof.

[0059] The content of the charge control agent is preferably 0.1 parts by mass or more and 10 parts by mass or less, and more preferably 0.5 parts by mass or more and 5 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0060] 1-1-2.External additives The white toner particles may further contain an external additive in order to improve the fluidity and chargeability of the white toner. The external additive is attached to the surface of the white toner base particles as a post-treatment agent.

[0061] For the purpose of controlling fluidity and chargeability, conventionally known metal oxide particles can be used as the external additive, and examples thereof include silica particles, titania particles, alumina particles, zirconia particles, zinc oxide particles, chromium oxide particles, cerium oxide particles, antimony oxide particles, tungsten oxide particles, tin oxide particles, tellurium oxide particles, manganese oxide particles, and boron oxide particles. These may be used alone or in combination of two or more kinds.

[0062] The external additive may also contain organic fine particles such as homopolymers of styrene, methyl methacrylate, etc., or copolymers thereof.

[0063] The external additive may contain a lubricant to further improve cleaning properties and transfer properties. Examples of the lubricant include metal salts of higher fatty acids such as zinc, aluminum, copper, magnesium, calcium, etc. of stearic acid, zinc, manganese, iron, copper, magnesium, etc. of oleic acid, zinc, copper, magnesium, etc. of palmitic acid, zinc, calcium, etc. of linoleic acid, zinc, calcium, etc. of ricinoleic acid, etc. of zinc, calcium, etc.

[0064] The shape of the external additive is not limited, and may be any of spherical, flat, plate-like, and needle-like.

[0065] The content of the external additive is preferably from 1 to 7 parts by weight, and more preferably from 2 to 4 parts by weight, per 100 parts by weight of the toner base particles.

[0066] 1-1-3. Physical properties of white toner (Volume-based median diameter (D50)) The volume-based median diameter (D50) of the white toner base particles is preferably, for example, 3.0 μm or more and 10.0 μm or less, and preferably 5.0 μm or more and 8.0 μm or less. By making the D50 of the white toner base particles 3.0 μm or more, the gap between the particles is also moderately large, so that the frictional force received by the fixing belt can be further reduced. That is, by making the particle size a certain size or more, it is easier to ensure a certain size or more of gap between the particles, so that it is easier to ensure an opportunity to disperse the frictional force of the belt received during fixing, and it is possible to further suppress belt breakage. When the particle size of the white toner base particles is 10.0 μm or less, not only can finer dot images be faithfully reproduced, but also less heat energy is required for melting, so that the fixability is better.

[0067] The D50 of the white toner base particles may be the same as or different from that of the color toner base particles. In particular, from the viewpoint of easier maintenance of fixability to a recording medium, it is preferable that the D50 of the white toner base particles is larger than that of the color toner base particles so that the toner in the upper layer melts and spreads to cover the white toner in the lower layer.

[0068] The volume-based median diameter (D50) can be measured and calculated using, for example, a device such as a "Multisizer 3 (Beckman Coulter)" connected to a computer system for data processing. The measurement procedure is as follows: 0.02g of toner particles are mixed with 20ml of surfactant solution (for example, a surfactant solution prepared by diluting a neutral detergent containing surfactant components 10 times with pure water to disperse the toner particles), and then ultrasonic dispersion is performed for 1 minute to prepare a toner particle dispersion. This toner particle dispersion is pipetted into a beaker containing an ISOTON II (manufactured by Beckman Coulter) in a sample stand until the measurement concentration is 5-10%, and the measurement is performed by setting the measurement count to 25,000 particles. The aperture diameter of the Multisizer 3 is 100μm. The measurement range of 1-30μm is divided into 256 parts to calculate the frequency, and the particle diameter with the largest volume cumulative fraction of 50% is taken as the volume-based median diameter (D50).

[0069] When the toner is obtained by a pulverization method, the D50 of the white toner base particles can be controlled mainly by the pulverization conditions (rotation speed of the pulverizer, pulverization time) and classification conditions.

[0070] (Average circularity) The average circularity of the white toner base particles is not particularly limited, but is preferably, for example, 0.920 or more and 0.955 or less. When the average circularity of the white toner base particles is 0.920 or more, it is easy to improve the charge rise and fluidity. When the average circularity of the white toner base particles is 0.955 or less, appropriate gaps can be formed between the particles, so that the frictional force received when the fixing belt slides against the toner layer can be further reduced. From the same viewpoint, the average circularity of the white toner base particles is more preferably 0.940 or more and 0.953 or less.

[0071] The average circularity of the white toner base particles can be measured by the following method. The toner particles are wetted with a surfactant solution and ultrasonically dispersed for 1 minute. After dispersion, a flow type particle image analyzer "FPIA-3000" (manufactured by Sysmex) is used to measure the particles in the HPF (high magnification imaging) mode under the measurement conditions at an appropriate concentration of 3,000 to 10,000 HPF detections. Within this range, reproducible measurement values ​​can be obtained. The circularity is calculated using the following formula. Circularity = (perimeter of a circle with the same projected area as the particle image) / (perimeter of the projected particle image) The average circularity is the arithmetic mean value obtained by adding up the circularity of each particle and dividing the sum by the total number of particles measured.

[0072] The average circularity of the white toner base particles may be the same as or different from that of the color toner base particles, and from the viewpoint of reducing friction between the fixing belt and the toner image, it is preferable that the average circularity of the white toner base particles is lower than that of the color toner base particles.

[0073] The average circularity of the white toner base particles can be adjusted by the toner production method described below, the conditions of the heat treatment of the toner base particles, etc. For example, toner base particles produced by a pulverization method tend to have a low average circularity.

[0074] (moisture content) The moisture content of the white toner is, for example, preferably 0.1% to 0.6%, more preferably 0.2% to 0.5%. When the moisture content is 0.6% or less, the amount of moisture contained in the toner that evaporates due to heating during fixing can be reduced. Therefore, hydrolysis of the coating resin (PI) of the fixing belt can be reduced, and belt wear can be suppressed. When the moisture content is 0.1% or more, the toner can be made less likely to be charged, so that charging caused by rubbing between the toner and the fixing belt surface can be suppressed, and scattering of the toner can be suppressed.

[0075] The moisture content of the white toner may be the same as or different from that of the color toner. In particular, from the viewpoint of reducing friction with the fixing belt, it is preferable that there is no difference in moisture content. Therefore, it is preferable that the moisture content of the white toner in the lower layer, where the moisture content is less likely to evaporate during fixing, is the same as or less than that of the color toner.

[0076] The moisture content of white toner can be adjusted by the toner manufacturing method and drying conditions. For example, toner manufactured by the pulverization method tends to have a lower moisture content than toner manufactured by the emulsion aggregation method or suspension polymerization method. In addition, the moisture content of toner tends to decrease when the drying time is extended or the drying temperature is increased.

[0077] 1-2. Color toner The color toner is a toner that imparts a predetermined color tone to an image. The color toner includes color toner particles. The color toner particles include color toner base particles, and may further include an external additive attached to the surface thereof as necessary.

[0078] 1-2-1. Color toner base particles The color toner base particles contain a binder resin and a colorant.

[0079] (Binding resin) The binder resin contained in the color toner base particles may be any of an amorphous resin, a crystalline resin, and a hybrid resin, as in the white toner base particles. Among them, the binder resin contained in the color toner base particles preferably contains a crystalline polyester resin and an amorphous polyester resin.

[0080] The polycarboxylic acid and polyhydric alcohol constituting the amorphous polyester resin contained in the color toner base particles may be the same as the polycarboxylic acid and polyhydric alcohol constituting the amorphous polyester resin contained in the white toner base particles. Similarly, the polycarboxylic acid and polyhydric alcohol constituting the crystalline polyester resin contained in the color toner base particles may be the same as the polycarboxylic acid and polyhydric alcohol constituting the crystalline polyester resin contained in the white toner base particles.

[0081] Among these, from the viewpoint of easily satisfying the relationship of the above formula (1), the polyvalent carboxylic acid of the amorphous polyester resin contained in the color toner base particles preferably contains an aliphatic carboxylic acid, and from the viewpoint of the scratch resistance of the toner image, it is more preferable to contain an unsaturated aliphatic carboxylic acid which is considered to exert the hardness of the resin, because this can appropriately lower the viscosity of the color toner near the fixing temperature.

[0082] The range of the content ratio of the amorphous polyester resin to the crystalline polyester resin in the color toner base particles can be the same as the range of the content ratio of the amorphous polyester resin to the crystalline polyester resin in the white toner base particles.

[0083] The total amount of the amorphous polyester resin and the crystalline polyester resin in the color toner base particles is preferably 10% by mass or more, and more preferably 15% by mass or more and 50% by mass or less, based on the binder resin.

[0084] The content of the binder resin in the color toner base particles is preferably 70% by mass or more and 90% by mass or less, and more preferably 75% by mass or more and 87% by mass or less, based on the mass of the color toner base particles.

[0085] (Coloring agent) As the colorant, a pigment can be used. The color toner base particles may contain a colorant such as yellow, magenta, cyan, or black, depending on the color tone to be exhibited by the color toner. The color toner base particles may contain only one type of colorant, or may contain a combination of multiple types of colorants.

[0086] Examples of colorants contained in yellow toners include CI Solvent Yellow 19, 44, 77, 79, 81, 82, 93, 98, 103, 104, 112, and 162; CI Pigment Yellow 14, 17, 74, 93, 94, 138, 155, 180, and 185.

[0087] Examples of colorants contained in magenta toners include CI Solvent Red 1, 49, 52, 58, 63, 111, 122, CI Pigment Red 5, 48:1, 53:1, 57:1, 122, 139, 144, 149, 166, 177, 178, and 222.

[0088] An example of a colorant contained in a cyan toner is CI Pigment Blue 15:3.

[0089] Examples of colorants contained in black toner include carbon black, magnetic materials, titanium black, etc. Examples of carbon black include channel black, furnace black, acetylene black, thermal black, lamp black, etc. Examples of magnetic materials include ferromagnetic metals such as iron, nickel, and cobalt, alloys containing these ferromagnetic metals, compounds of ferromagnetic metals such as ferrite and magnetite, and alloys that do not contain ferromagnetic metals but exhibit ferromagnetism when heat-treated. Examples of alloys that exhibit ferromagnetism when heat-treated include Heusler alloys such as manganese-copper-aluminum and manganese-copper-tin, and chromium dioxide.

[0090] The content of the colorant is not particularly limited, but is preferably from 1 to 20 parts by mass, and more preferably from 10 to 17 parts by mass, per 100 parts by mass of the binder resin.

[0091] 1-2-2.External additives The color toner particles may further contain an external additive. The external additive is attached to the surface of the color toner base particles as a post-treatment agent. As the external additive, the same external additive as that in the white toner particles described above can be used.

[0092] 1-2-2. Properties of color toner The volume-based median diameter (D50) of the color toner base particles, the average circularity, and the moisture content of the color toner can each be within the same range as above. It is.

[0093] In particular, from the viewpoint of easier maintenance of fixability to a recording medium of a toner layer in which a color toner is superimposed on a white toner, the D50 of the color toner base particles is preferably smaller than that of the white toner base particles, so that the toner in the upper layer melts and spreads to cover the white toner in the lower layer. In addition, from the viewpoint of reducing friction between a fixing belt and a toner image, it is preferable that the average circularity of the color toner base particles is also high.

[0094] 1-3.Common matters The white toner and the color toner may each be a one-component developer, or may be a two-component developer containing toner particles and carrier particles. In the present embodiment, it is preferable that the white toner and the color toner are both one-component developers.

[0095] 1-4. Manufacturing method of white toner and color toner The white toner and the color toner can be produced by a pulverization method, an emulsion dispersion method, a suspension polymerization method, a dispersion polymerization method, an emulsion polymerization method, an emulsion polymerization aggregation method, or the like. Among them, the pulverization method and the emulsion polymerization aggregation method are preferred, and the pulverization method is more preferred. The toner base particles produced by the pulverization method are irregular particles, so that appropriate gaps are easily formed between the particles. This makes it easier to reduce the frictional force of the fixing belt that is received from the toner image during fixing.

[0096] In the pulverization method, the binder resin and the colorant are melted and kneaded, and then cooled to obtain a resin composition, which is then pulverized to obtain toner base particles. After the pulverization process, classification and drying processes may be performed as necessary.

[0097] (Mixing / melting) First, the materials that make up the toner base particles (binder resin, colorant, etc.) are mixed. Mixing can be performed using a mixing device such as a double con mixer, V-type mixer, drum mixer, super mixer, Henschel mixer, Nauta mixer, or Mechano Hybrid.

[0098] Next, the mixed materials are melt-kneaded. For melt-kneading, a batch-type kneader such as a pressure kneader and a Banbury mixer, or a continuous kneader can be used. For continuous production, it is preferable to use a single-screw extruder or a twin-screw extruder. Examples of twin-screw extruders include a KTK type twin-screw extruder (manufactured by Kobe Steel, Ltd.), a TEM type twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), a PCM kneader (manufactured by Ikegai Co., Ltd.), a twin-screw extruder (manufactured by KCK Corporation), a Co-Kneader (manufactured by Buss Co., Ltd.), and a Kneadex (manufactured by Nippon Coke and Engineering Co., Ltd.). The temperature of the melt-kneading is preferably about 100 to 200°C. The resin composition obtained by melt-kneading is rolled with a two-roller or the like, and quenched with water or the like to form a solid.

[0099] (Crushing) The resin composition thus obtained is pulverized to a desired particle size by, for example, coarsely pulverizing the resin composition with a pulverizer such as a crusher, a hammer mill, or a feather mill, and then finely pulverizing the resin composition with a fine pulverizer such as a Cryptron System (manufactured by Kawasaki Heavy Industries, Ltd.), a Super Rotor (manufactured by Nisshin Engineering Inc.), or a Turbo Mill (manufactured by Freund Turbo Corp.), or a fine pulverizer using an air jet system.

[0100] (classification) Thereafter, the pulverized resin composition is classified as necessary. Classification can be performed using a classifier or sieve such as an inertial classification type Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), a centrifugal classification type Turboplex (manufactured by Hosokawa Micron Corporation), a TSP Separator (manufactured by Hosokawa Micron Corporation), and a Faculty (manufactured by Hosokawa Micron Corporation).

[0101] (Dry) Furthermore, the resin composition after classification may be dried as necessary. The drying method is not particularly limited, and examples thereof include methods using an oven, a spray dryer, a vacuum freeze dryer, a reduced pressure dryer, a stationary shelf dryer, a mobile shelf dryer, a fluidized bed dryer, a rotary dryer, an agitator dryer, etc. In this manner, the toner base particles can be produced by the pulverization method.

[0102] (Addition of external additives) The obtained toner base particles may be used as is, or may be treated with an external additive as necessary. The external addition treatment may be performed by mixing a predetermined amount of the toner base particles and the external additive, and stirring and mixing the mixture with a mixing device such as a double con mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.), or a Nobilta (manufactured by Hosokawa Micron Corporation).

[0103] Next, an image forming method using the above-mentioned white toner and color toner will be described.

[0104] 2. Image forming method [Configuration of image forming device] An image forming apparatus that can be used in this embodiment will now be described.

[0105] Fig. 2 is a schematic diagram showing an example of the image forming apparatus 1 according to the present embodiment. Fig. 3 is an enlarged schematic diagram of a main part of the fixing unit 60 in Fig. 2.

[0106] The image forming apparatus 1 shown in FIG. 2 includes an image processing section 30, an image forming section 40, a conveying section 50, a fixing section 60, and an image reading section .

[0107] Image forming section 40 has image forming units 41Y, 41M, 41C, 41K, and 41W that form images using toner of each color, Y (yellow), M (magenta), C (cyan), K (black), and W (white). Since these all have the same configuration except for the toner contained therein, hereinafter, the symbols representing the colors may be omitted. Image forming section 40 further has an intermediate transfer unit 42 and a secondary transfer unit 43. These correspond to transfer devices.

[0108] The image forming unit 41 includes an exposure device 411, a development device 412, an electrophotographic photoconductor (image carrier) 413, a charging device 414, and a drum cleaning device 415. The charging device 414 is, for example, a corona charger. The charging device 414 may be a contact charging device that charges the electrophotographic photoconductor 413 by contacting a contact charging member such as a charging roller, a charging brush, or a charging blade with the electrophotographic photoconductor 413. The exposure device 411 includes, for example, a semiconductor laser as a light source, and a light deflection device (polygon motor) that irradiates the electrophotographic photoconductor 413 with laser light according to an image to be formed. The electrophotographic photoconductor 413 is a negatively charged organic photoconductor having photoconductivity. The electrophotographic photoconductor 413 is charged by the charging device 414.

[0109] The developing device 412 is a two-component developing device. The developing device 412 has, for example, a developing container that contains a two-component developer, a developing roller (magnetic roller) that is rotatably arranged at the opening of the developing container, a partition that divides the inside of the developing container so that the two-component developer can communicate with each other, a transport roller for transporting the two-component developer on the opening side of the developing container toward the developing roller, and a stirring roller for stirring the two-component developer in the developing container. The developing container contains, for example, a two-component developer.

[0110] The intermediate transfer unit 42 includes an intermediate transfer belt (intermediate transfer body) 421, a primary transfer roller 422 that presses the intermediate transfer belt 421 against the electrophotographic photosensitive body 413, a plurality of support rollers 423 including a backup roller 423A, and a belt cleaning device 426. The intermediate transfer belt 421 is stretched in a loop shape around the plurality of support rollers 423. By rotating at least one drive roller among the plurality of support rollers 423, the intermediate transfer belt 421 runs at a constant speed in the direction of arrow A.

[0111] The belt cleaning device 426 has an elastic member 426a. The elastic member 426a comes into contact with the intermediate transfer belt 421 after the secondary transfer, and removes deposits on the surface of the intermediate transfer belt 421. The elastic member 426a is made of an elastic body, and includes a cleaning blade, a brush, and the like.

[0112] The secondary transfer unit 43 includes an endless secondary transfer belt 432 and a plurality of support rollers 431 including a secondary transfer roller 431A. The secondary transfer belt 432 is stretched by the secondary transfer roller 431A and the support rollers 431 in a loop shape.

[0113] The fixing unit 60 includes a fixing belt 61 (circular belt), a heater 62 (heating member), and a pressure roller 63 (opposing member).

[0114] The heater 62 is disposed on the inner peripheral surface side of the fixing belt 61 and heats the fixing belt 61 from the inner peripheral side. The heater 62 is a pad member having a substantially rectangular parallelepiped shape, and presses the circular belt 61 with one surface of the rectangular parallelepiped to form a planar fixing nip. The pressure roller 63 (opposing member) is disposed on the outer circumferential surface side of the fixing belt 61, and faces the heater 62 with the fixing belt 61 interposed therebetween. A nip is formed between the outer circumferential surface of the fixing belt 61 and the pressure roller 63. As a result, the fixing unit 60 fixes the toner image on the conveyed recording medium S at the opposing position. Specifically, when the recording medium S passes through the nip, the fixing unit 60 applies heat and pressure to the toner image to fix it on the recording medium S. The fixing unit 60 configured in this manner is also called a surf fixing type.

[0115] A lubricating sheet (not shown) may be interposed between the heater 62 and the fixing belt 61 to enable smooth rotation of the fixing belt 61. The lubricating sheet may be, for example, a polyimide sheet coated with polytetrafluoroethylene (PTFE) having a thickness of 100 μm.

[0116] The image forming apparatus 1 further includes an image reading section 70, an image processing section 30, and a transport section 50. The image reading section 70 includes a paper feeder 71 and a scanner 72. The transport section 50 includes a paper feed section 51, a paper discharge section 52, and a transport path section 53. The three paper feed tray units 51a to 51c constituting the paper feed section 51 accommodate recording media S identified based on basis weight and size according to preset types. The transport path section 53 includes a plurality of transport roller pairs, such as a registration roller pair 53a.

[0117] The image forming apparatus 1 configured as above performs each process described below under the control of a control unit (not shown).

[0118] The type of recording medium S is not particularly limited, and may be paper, a film label, or a film. A film label refers to one with a release paper attached, while a film refers to one with neither a release paper nor an adhesive attached.

[0119] Examples of films and the film portion of film labels include polypropylene film, polyethylene film, polyvinyl chloride film, polyethylene terephthalate film, polystyrene film, polyester film, and polylactic acid film. Among these, polypropylene film or polyethylene terephthalate film is preferred from the standpoint of versatility, etc.

[0120] Polypropylene films and polyethylene terephthalate films are used for various labels, packages, etc. These films may be appropriately surface-treated for the purpose of improving printability. These films may be transparent films, or may contain pigments or the like and have any color, such as white, and may have a toner-receiving layer formed on the surface.

[0121] [Image forming method] Next, a method for forming a full-color image using an image forming apparatus will be specifically described.

[0122] The scanner 72 optically scans and reads the document D on the contact glass. The reflected light from the document D is read by the CCD sensor 72a and becomes input image data. The input image data is subjected to predetermined image processing in the image processing unit 30 and sent to the exposure device 411.

[0123] The electrophotographic photoreceptor 413 rotates at a constant peripheral speed. The charging device 414 uniformly charges the surface of the electrophotographic photoreceptor 413 to a negative polarity (charging process). In the exposure device 411, the polygon mirror of the polygon motor rotates at high speed, and laser light corresponding to input image data of each color component is developed along the axial direction of the electrophotographic photoreceptor 413 and irradiated onto the outer circumferential surface of the electrophotographic photoreceptor 413 along the axial direction. In this way, an electrostatic latent image is formed on the surface of the electrophotographic photoreceptor 413 (exposure process).

[0124] In the developing device 412, the toner base particles are charged by stirring and transporting the two-component developer in the developing container, and the two-component developer is transported to a developing roller, which forms a magnetic brush on the surface of the developing roller. The charged toner base particles electrostatically adhere from the magnetic brush to the electrostatic latent image on the electrophotographic photoreceptor 413. In this way, the electrostatic latent image on the surface of the electrophotographic photoreceptor 413 is visualized, and a toner image corresponding to the electrostatic latent image is formed on the surface of the electrophotographic photoreceptor 413 (developing process). Note that the "toner image" refers to a state in which toner is gathered in an image shape.

[0125] The toner image on the surface of the electrophotographic photoreceptor 413 is transferred to an intermediate transfer belt 421 by an intermediate transfer unit 42. Residual toner remaining on the surface of the electrophotographic photoreceptor 413 after the transfer is removed by a drum cleaning device 415 having a drum cleaning blade that is in sliding contact with the surface of the electrophotographic photoreceptor 413.

[0126] The intermediate transfer belt 421 is pressed against the electrophotographic photoreceptor 413 by the primary transfer roller 422, whereby a primary transfer nip is formed for each electrophotographic photoreceptor by the electrophotographic photoreceptor 413 and the intermediate transfer belt 421. In the primary transfer nip, the toner images of each color are transferred to the intermediate transfer belt 421 in order, superimposed thereon (primary transfer step). In this embodiment, when the intermediate transfer belt 421 is transported in the direction of the arrow A, the toner images of each color are transferred in the order of Y, M, C, K, and W (see FIG. 2).

[0127] Meanwhile, secondary transfer roller 431A is pressed against backup roller 423A via intermediate transfer belt 421 and secondary transfer belt 432. As a result, a secondary transfer nip is formed by intermediate transfer belt 421 and secondary transfer belt 432. Recording medium S passes through the secondary transfer nip. Recording medium S is transported to the secondary transfer nip by transport unit 50. Correction of the inclination of recording medium S and adjustment of transport timing are performed by a registration roller unit in which registration roller pair 53a is arranged.

[0128] When the recording medium S is transported to the secondary transfer nip, a transfer bias is applied to the secondary transfer roller 431A. By applying this transfer bias, the toner image carried on the intermediate transfer belt 421 is transferred to the recording medium S (a process of forming a toner image on the recording medium). In this embodiment, the toner images of each color are transferred onto the recording medium S in the order of W, K, C, M, and Y (see FIG. 2).

[0129] In this manner, the white toner image and the color toner image are transferred in this order onto the recording medium S. As a result, a toner image (toner layer T) is formed on the recording medium S in which the white toner image and the color toner image are arranged in this order (see FIG. 1B).

[0130] The amount of white toner Mw is, for example, 5 g / m 2 More than 10g / m 2 The adhesion amount Mc of the color toner image is preferably 4 g / m or less. 2 More than 10g / m 2It can be as follows:

[0131] The total amount of the white toner image and the color toner image is, for example, 9 g / m 2 More than 20g / m 2 It is preferable that the thickness is less than 12 g / m 2 More than 18g / m 2 When the total amount is equal to or greater than the lower limit, an image of higher density can be formed, and when the total amount is equal to or less than the upper limit, fixability to a recording medium can be more easily maintained.

[0132] The ratio of the adhesion amount Mw of the white toner image to the adhesion amount Mc of the color toner image is preferably 0.5 or more and 2.2 or less, depending on the desired color development, etc. When Mw / Mc is 0.5 or more, the color development of the image is more likely to be improved. When Mw / Mc is 2.2 or less, the adhesion amount of the color toner that melts easily is larger, so that the low-temperature fixability is more likely to be improved and image blisters caused by unevenness of unmelted particles are more likely to be reduced.

[0133] The recording medium S onto which the toner image has been transferred is transported by the secondary transfer belt 432 toward the fixing unit 60 .

[0134] Next, the recording medium is sent to a fixing section 60, where the full-color toner image is fixed onto the recording medium (a process for fixing the toner image onto the recording medium).

[0135] In this embodiment, the fixing unit 60 nips the recording medium S on which the toner image has been formed between the fixing belt 61 and the pressure roller 63 which faces the fixing belt 61 via the heater 62 and the fixing belt 61. Specifically, the fixing nip is formed by pinching the rotating fixing belt 61, and the conveyed recording medium S is heated and pressurized in the fixing nip portion. As a result, the toner image is fixed onto the recording medium S.

[0136] The heating temperature of the toner image is preferably 130° C. or higher and 170° C. or lower, and more preferably 130° C. or higher and 150° C. or lower. When the heating temperature is within the above range, the toner image can be fixed at a low temperature without impairing the fixability of the toner image. The heating temperature can be confirmed as the set temperature of the heater 62.

[0137] The recording medium S on which the toner image has been fixed is discharged outside the apparatus by a paper discharge section 52 equipped with a paper discharge roller 52a.

[0138] Any deposits such as residual toner remaining on the surface of the intermediate transfer belt 421 after the secondary transfer are removed by a belt cleaning device 426 having a cleaning blade that is in sliding contact with the surface of the intermediate transfer belt 421. At this time, since the above-mentioned intermediate transfer body is used as the intermediate transfer belt, the dynamic frictional force can be reduced over time.

[0139] As described above, in the above embodiment, an image is formed by a method including the steps of 1) forming a toner image on a recording medium, the toner image including a white toner image and a color toner image disposed thereon, and 2) fixing the formed toner image on the recording medium. In the above-mentioned 2) process of fixing the toner image, the recording medium S on which the toner image has been formed is nipped between the fixing belt 61 and the pressure roller 63 opposed via the heater 62 and the circular belt 61, thereby fixing the toner image onto the recording medium S. The white toner and the color toners satisfy the relationship of the above-mentioned formula (1).

[0140] As a result, the toner layer surface becomes less viscous and melts, while the inside of the toner layer does not melt completely, and some gaps are maintained between the particles. This makes it easier for the frictional force generated in the nip to be dispersed among the contact areas between the toner base particles, and reduces the friction. As a result, it is possible to prevent the image surface from becoming rough and to suppress breakage of the fixing belt.

[0141] It should be noted that the above-described image forming apparatus and image forming method are merely illustrative embodiments for carrying out the present invention, and the present invention is not limited to these.

[0142] For example, the image forming apparatus in the above embodiment is an example of a tandem type image forming apparatus configured with five types of developing devices, namely, yellow, magenta, cyan, black, and white, and five electrophotographic photosensitive members provided for each color, but is not limited to this, and may be a five-cycle type image forming apparatus configured with five types of developing devices, namely, yellow, magenta, cyan, black, and white, and one electrophotographic photosensitive member.

[0143] In the above embodiment, a two-component developing device is used as developing device 412, but the present invention is not limited to this, and a one-component developing device may be used. EXAMPLES

[0144] The present invention will now be described with reference to examples, which should not be construed as limiting the scope of the present invention.

[0145] 1. Toner Materials 1-1. Amorphous polyester resin (for white toner) (Production Example of Amorphous Polyester Resin SA1) Terephthalic acid: 40.2 parts Bisphenol A propylene oxide adduct (BPA-PO): 29.0 parts Dipropanol: 30.8 parts Tin 2-ethylhexanoate (esterification catalyst): 0.5 parts The above materials were weighed into a reaction vessel equipped with a condenser, stirrer, nitrogen inlet, and thermocouple. After the atmosphere in the reaction vessel was replaced with nitrogen gas, the temperature was gradually raised with stirring, and the reaction was carried out for 3 hours at a temperature of 140° C. with stirring. Next, the pressure inside the reaction vessel was reduced to 8.0 kPa, and the temperature was raised to 200° C. with stirring, and the reaction was carried out for 4 hours. Thereafter, the pressure inside the reaction vessel was reduced again to 5 kPa or less, and the mixture was reacted at 200° C. for 3 hours to obtain amorphous polyester resin SA1.

[0146] (Production Example of Amorphous Polyester Resin SA2) Terephthalic acid: 40.2 parts Bisphenol A propylene oxide adduct (BPA-PO): 29.0 parts Dipropanol: 30.8 parts Tin 2-ethylhexanoate (esterification catalyst): 0.5 parts The above materials were weighed into a reaction vessel equipped with a condenser, stirrer, nitrogen inlet, and thermocouple. After the atmosphere in the reaction vessel was replaced with nitrogen gas, the temperature was gradually raised with stirring, and the reaction was carried out for 3 hours at a temperature of 140° C. with stirring. Next, the pressure inside the reaction vessel was reduced to 8.0 kPa, and the temperature was raised to 200° C. with stirring, and the reaction was carried out for 6 hours. Thereafter, the pressure inside the reaction vessel was reduced again to 5 kPa or less, and the mixture was reacted at 200° C. for 5 hours to obtain amorphous polyester resin SA2.

[0147] (Production Example of Amorphous Polyester Resin SA3 (Dispersion)) In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 25.3 parts of terephthalic acid, 5.6 parts of adipic acid, 30.9 parts of an ethylene oxide 2.2 mol adduct of bisphenol A, 34.3 parts of a propylene oxide 2.2 mol adduct of bisphenol A, and 0.2 parts of dibutyltin oxide were added. The mixture was reacted at 230°C under normal pressure for 3 hours. Then, 4 parts of trimellitic acid were added and reacted for another 2 hours. Then, the mixture was reacted under a reduced pressure of 10 to 15 mmHg for 5 hours to obtain an amorphous polyester resin. 100 parts of this amorphous polyester resin was dissolved in 90 parts of acetone to obtain an acetone solution. 180 parts of the obtained acetone solution and 720 parts of water were mixed and mixed at 8,000 rpm for 1 minute using a TK homomixer. Thereafter, the dispersion was decompressed, and the acetone was volatilized and removed to obtain an amorphous polyester resin dispersion SA3.

[0148] (Production Example of Amorphous Polyester Resin SA4 (Dispersion)) In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 25.3 parts of terephthalic acid, 5.6 parts of adipic acid, 32.2 parts of an ethylene oxide 2.2 mol adduct of bisphenol A, 35.7 parts of a propylene oxide 2.2 mol adduct of bisphenol A, and 0.2 parts of dibutyltin oxide were added. The mixture was reacted at 230°C under normal pressure for 3 hours. Then, 4 parts of trimellitic acid were added and reacted for another 2 hours. Then, the mixture was reacted for 5 hours under a reduced pressure of 10 to 15 mmHg. As a result, amorphous polyester resin SL1 was obtained. Next, 25.3 parts of terephthalic acid, 5.6 parts of adipic acid, 30.9 parts of an ethylene oxide 2.2 mol adduct of bisphenol A, 34.3 parts of a propylene oxide 2.2 mol adduct of bisphenol A, and 0.2 parts of dibutyltin oxide were added to a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube. The mixture was reacted at 230°C for 3 hours under normal pressure. Then, 4 parts of trimellitic acid were added and reacted for another 2 hours. After that, the mixture was reacted for 5 hours under a reduced pressure of 10 to 15 mmHg. As a result, an amorphous polyester resin SH1 was obtained. 95 parts of amorphous polyester resin L1 and 5 parts of amorphous polyester resin H1 were dissolved in 90 parts of acetone to obtain an acetone solution. 180 parts of the obtained acetone solution and 720 parts of water were mixed and mixed at 8,000 rpm for 1 minute using a TK homomixer (manufactured by Primix Corporation). Thereafter, the dispersion was decompressed, and the acetone was volatilized and removed to obtain an amorphous polyester resin dispersion SA4.

[0149] 1-2.Crystalline polyester resin (for white toner) (Production example of crystalline polyester SB1) Adipic acid: 55.3 parts Bisphenol A propylene oxide adduct (BPA-PO: 44.7 parts Tin 2-ethylhexanoate: 0.5 parts The above materials were weighed into a reaction vessel equipped with a cooling tube, a stirrer, a nitrogen inlet tube, and a thermocouple. After replacing the inside of the reaction vessel with nitrogen gas, the temperature was gradually raised while stirring, and the reaction was carried out for 3 hours while stirring at a temperature of 140°C. Next, the pressure in the reaction vessel was reduced to 8.3 kPa, and the temperature was raised to 200°C while stirring, and the reaction was carried out for 1 hour. As a result, crystalline polyester SB1 was obtained.

[0150] (Production example of crystalline polyester SB2) Adipic acid: 55.3 parts Bisphenol A propylene oxide adduct (BPA-PO: 44.7 parts Tin 2-ethylhexanoate: 0.5 parts The above materials were weighed into a reaction vessel equipped with a cooling tube, a stirrer, a nitrogen inlet tube, and a thermocouple. After replacing the inside of the reaction vessel with nitrogen gas, the temperature was gradually raised while stirring, and the reaction was carried out for 3 hours at a temperature of 150°C while stirring. Next, the pressure in the reaction vessel was reduced to 8.3kPa, and the temperature was raised to 200°C while stirring, and the reaction was carried out for 3 hours to obtain crystalline polyester SB2.

[0151] (Production example of crystalline polyester SB3) In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 682 parts of bisphenol A ethylene oxide 2 mole adduct, 81 parts of bisphenol A propylene oxide 2 mole adduct, 283 parts of terephthalic acid, 22 parts of trimellitic anhydride, and 2 parts of dibutyltin oxide were charged and reacted at 230°C under normal pressure for 8 hours. Then, the mixture was reacted under reduced pressure of 10 to 15 mmHg for 5 hours to synthesize an intermediate polyester. The intermediate polyester obtained had a number average molecular weight (Mn) of 2,100, a weight average molecular weight (Mw) of 9,600, a glass transition temperature (Tg) of 55°C, an acid value of 0.5 mgKOH / g, and a hydroxyl value of 49 mgKOH / g. Next, 411 parts of the intermediate polyester, 89 parts of isophorone diisocyanate, and 500 parts of ethyl acetate were charged into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, and reacted at 100° C. for 5 hours to synthesize prepolymer 1. The free isocyanate content of the obtained prepolymer 1 was 1.60%, and the solids concentration of prepolymer 1 (at 150° C., After leaving it for 45 minutes, the percentage was 50%.

[0152] In a 5L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, 63.1 parts of sebacic acid and 36.9 parts of 1,6-hexanediol were charged. Then, together with titanium tetraisopropoxide (500 ppm relative to the resin component), the mixture was reacted at 180°C for 10 hours, then heated to 200°C and reacted for 3 hours, and further reacted at a pressure of 8.3 kPa for 2 hours. Thus, a crystalline polyester resin C1 was obtained. 25 parts of crystalline polyester resin SB3 and 75 parts of ethyl acetate were placed in a container equipped with a stirring rod and a thermometer, and the temperature was raised to 80°C under stirring to dissolve the crystalline polyester resin SB3. After cooling to 30°C, the mixture was dispersed using a bead mill, Ultraviscomill (manufactured by Imex), with a liquid delivery rate of 1 kg / h, a disk peripheral speed of 6 m / s, and 80% by volume of zirconia beads with a diameter of 0.5 mm, in three passes to obtain a crystalline polyester resin dispersion SB3.

[0153] 1-3. Amorphous polyester resin (for colored toner) (Production Example of Amorphous Polyester Resin A1) Fumaric acid: 48.2 parts Bisphenol A propylene oxide adduct (BPA-PO): 21.0 parts Dipropanol: 30.8 parts · Tin 2-ethylhexanoate (esterification catalyst): 0.5 parts The above materials were weighed into a reaction vessel equipped with a condenser, stirrer, nitrogen inlet, and thermocouple. After the atmosphere in the reaction vessel was replaced with nitrogen gas, the temperature was gradually raised with stirring, and the reaction was carried out for 3 hours at a temperature of 140° C. with stirring. Next, the pressure inside the reaction vessel was reduced to 8.0 kPa, and the temperature was raised to 200° C. with stirring, and the reaction was carried out for 4 hours. Thereafter, the pressure inside the reaction vessel was reduced again to 5 kPa or less, and the mixture was reacted at 200° C. for 3 hours to obtain amorphous polyester resin A1.

[0154] (Production Example of Amorphous Polyester Resin A2) Fumaric acid: 48.2 parts Bisphenol A propylene oxide adduct (BPA-PO): 21.0 parts Dipropanol: 30.8 parts · Tin 2-ethylhexanoate (esterification catalyst): 0.5 parts The above materials were weighed into a reaction vessel equipped with a condenser, stirrer, nitrogen inlet, and thermocouple. After the atmosphere in the reaction vessel was replaced with nitrogen gas, the temperature was gradually raised with stirring, and the mixture was reacted for 3 hours at a temperature of 150° C. with stirring. Next, the pressure inside the reaction vessel was reduced to 8.0 kPa, and the temperature was raised to 200° C. with stirring, and the reaction was carried out for 4 hours. Thereafter, the pressure inside the reaction vessel was reduced again to 5 kPa or less, and the mixture was reacted at 200° C. for 5 hours to obtain amorphous polyester resin A2.

[0155] (Production Example of Amorphous Polyester Resin A3) -Synthesis of amorphous (low molecular weight) polyester resin L1- In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 25.3 parts of terephthalic acid, 5.6 parts of adipic acid, 32.2 parts of an ethylene oxide 2.2 mol adduct of bisphenol A, 35.7 parts of a propylene oxide 2.2 mol adduct of bisphenol A, and 0.2 parts of dibutyltin oxide were added. The mixture was reacted at 230°C under normal pressure for 4 hours. Then, the mixture was reacted under reduced pressure of 10mmHg to 15mmHg for 5 hours. As a result, amorphous polyester resin L1 was obtained. -Synthesis of amorphous (low molecular weight) polyester resin H1- In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 25.3 parts of terephthalic acid, 5.6 parts of adipic acid, 30.9 parts of an ethylene oxide 2.2 mol adduct of bisphenol A, 34.3 parts of a propylene oxide 2.2 mol adduct of bisphenol A, and 0.2 parts of dibutyltin oxide were added. The mixture was reacted at 230°C under normal pressure for 3 hours. Then, 4 parts of trimellitic acid were added and reacted for another 2 hours. Then, the mixture was reacted for 5 hours under reduced pressure of 10mmHg to 15mmHg. As a result, amorphous polyester resin H1 was obtained. -Preparation of amorphous polyester resin dispersion- 95 parts of amorphous polyester resin L1 and 5 parts of amorphous polyester resin H1 were dissolved in 90 parts of acetone to obtain an acetone solution. 180 parts of the obtained acetone solution and 720 parts of water were mixed and mixed at 8,000 rpm for 1 minute using a TK homomixer (manufactured by Primix Corporation). Thereafter, the dispersion was decompressed to volatilize and remove the acetone, and the amorphous polyester was obtained. Thus, a polyester resin dispersion A3 was obtained.

[0156] 1-4.Crystalline polyester resin (for colored toner) (Production Example of Crystalline Polyester B1) Fumaric acid: 48.3 parts Bisphenol A propylene oxide adduct (BPA-PO: 51.7 parts Tin 2-ethylhexanoate: 0.5 parts The above materials were weighed into a reaction vessel equipped with a cooling tube, a stirrer, a nitrogen inlet tube, and a thermocouple. After replacing the inside of the reaction vessel with nitrogen gas, the temperature was gradually raised while stirring, and the reaction was carried out for 3 hours at a temperature of 140°C while stirring. Next, the pressure in the reaction vessel was reduced to 8.3kPa, and the temperature was raised to 200°C while stirring, and the reaction was carried out for 1 hour to obtain crystalline polyester B1.

[0157] (Production Example of Crystalline Polyester B2) Fumaric acid: 48.3 parts Propylene oxide adduct of bisphenol A (BPA-PO: 51.7 parts Tin 2-ethylhexanoate: 0.5 parts The above materials were weighed into a reaction vessel equipped with a cooling tube, a stirrer, a nitrogen inlet tube, and a thermocouple. After replacing the inside of the reaction vessel with nitrogen gas, the temperature was gradually raised while stirring, and the reaction was carried out for 3 hours at a temperature of 150°C while stirring. Next, the pressure in the reaction vessel was reduced to 8.3kPa, and the temperature was raised to 200°C while stirring, and the reaction was carried out for 3 hours to obtain crystalline polyester B2.

[0158] (Example of preparation of dispersion of crystalline polyester B3) In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 682 parts of ethylene oxide 2-mol bisphenol A adduct, 81 parts of propylene oxide 2-mol bisphenol A adduct, 283 parts of terephthalic acid, 22 parts of trimellitic anhydride, and 2 parts of dibutyltin oxide were charged and reacted at 230° C. under normal pressure for 8 hours. The reaction was carried out for 5 hours under reduced pressure of 1000 mmHg to synthesize an intermediate polyester. The intermediate polyester thus obtained had a number average molecular weight (Mn) of 2,100, a weight average molecular weight (Mw) of 9,600, a glass transition temperature (Tg) of 55°C, an acid value of 0.5 mgKOH / g, and a hydroxyl value of 49 mgKOH / g. Next, 411 parts of the intermediate polyester, 89 parts of isophorone diisocyanate, and 500 parts of ethyl acetate were charged into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, and reacted at 100° C. for 5 hours to synthesize prepolymer 1. The free isocyanate content of the obtained prepolymer 1 was 1.60%, and the solids concentration of prepolymer 1 (at 150° C., After leaving it for 45 minutes, the percentage was 50%. In a 5L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, 63.1 parts of sebacic acid and 36.9 parts of 1,6-hexanediol were charged. Then, together with titanium tetraisopropoxide (500 ppm relative to the resin component), the mixture was reacted at 180°C for 10 hours, then heated to 200°C and reacted for 3 hours, and further reacted at a pressure of 8.3 kPa for 2 hours. Thus, a crystalline polyester resin B3 was obtained.

[0159] 25 parts of crystalline polyester resin B3 and 75 parts of ethyl acetate were placed in a vessel equipped with a stirring rod and a thermometer, and the temperature was raised to 80°C under stirring to dissolve the crystalline polyester resin B3. After cooling to 30°C, the mixture was milled in a bead mill, Ultraviscomill (manufactured by Imex), with a liquid delivery rate of 1 kg / h, a disk peripheral speed of 7 m / s, and a diameter of 0.5 mm. The mixture was filled with 80 volume % of zirconia beads of size m and dispersed under three-pass conditions to obtain a dispersion of crystalline polyester resin B3.

[0160] 2. Toner Preparation 2-1. Preparation of white toner (Preparation of White Toner S1) Amorphous polyester resin SA1: 55 parts Crystalline polyester SB1: 45 parts Diester wax: 5 parts (melting point: 95°C) Titanium dioxide (white colorant): 45 parts The above materials were mixed in a Henschel mixer at 40 m s -1 The mixture was mixed at a rotation speed of 1000 and a rotation time of 5 min. Then, the mixture was kneaded in a twin-screw kneader set at a temperature of 130°C. The kneaded mixture was cooled and coarsely crushed to 1 mm or less in a hammer mill to obtain a coarsely crushed product. The coarsely crushed product was finely crushed in a mechanical grinder. Then, the precursor after fine grinding was classified for 20 minutes using a fine powder classifier (Faculty / Hosokawa Micron Co., Ltd.) under conditions of a classification rotor rotation speed of 130 s-1 and a dispersion rotor rotation speed of 120 s-1, to obtain particles with a volume-based median diameter of 7.3 μm. The classified particles were dried using an airflow dryer under the following operating conditions: hot air temperature: 130° C.; drying time: 30 minutes; white toner base particles were obtained.

[0161] Then, 1.0 parts by mass of hydrophobic silica particles A (number average primary particle size: 16 nm, hydrophobicity: 68) and 1.5 parts by mass of large-diameter silica particles B (number average primary particle size: 50 nm) were added to 100 parts by mass of the white toner base particles, and the mixture was mixed for 1 minute at a peripheral speed of 35 m / s using a Henschel mixer, then paused and mixed for another 5 minutes. The mixture was sieved using a mesh with an opening of 43 μm to obtain white toner particles S1.

[0162] (Preparation of White Toners S2, S3, and S8) White toners S2 and S3 were produced in the same manner as white toner S1, except that the contents of the amorphous polyester resin and the crystalline polyester resin were changed as shown in Table 1 in the preparation of white toner S1.

[0163] (Preparation of White Toners S4 and S6) White toners S4 and S6 were prepared in the same manner as white toner S1, except that the drying conditions were changed as shown in Table 1 in the preparation of white toner S1.

[0164] (Preparation of White Toner S5) White toner S5 was prepared in the same manner as white toner S1, except that the types of amorphous polyester resin and crystalline polyester resin were changed as shown in Table 1 in the preparation of white toner S1.

[0165] (Manufacturing of white toner S7) 100 parts of amorphous polyester resin dispersion SA3, 120 parts of crystalline polyester resin dispersion SB3, 125 parts of wax dispersion, 12 parts of a master batch of an organically modified layered inorganic compound, 60 parts of titanium oxide, and 63 parts of ethyl acetate were mixed and mixed for 120 minutes at 6,000 rpm using a homomixer to obtain an oil phase 01 (solid content 50%). 180 parts of the aqueous phase was placed in a vessel equipped with a stirrer and a thermometer, and then kept at 20°C on a water bath. Next, 5 parts of modified prepolymer 1 were added to 111 parts of oil phase 01 kept at 20°C, and the mixture was poured into the aqueous phase. While keeping the temperature at 20°C, the mixture was mixed at 6,000 rpm for 2 minutes using a TK homomixer to obtain an emulsified slurry. The emulsified slurry was placed in a vessel equipped with a stirrer and a thermometer, and the solvent was removed under reduced pressure at 40°C to obtain a slurry with a solid content of 80% in the oil droplets. The obtained slurry was mixed at 6,000 rpm for 5 minutes using a TK homomixer while maintaining the temperature at 40°C. The slurry was subjected to shear stress and then desolvated under reduced pressure at 40°C to obtain a slurry with 0% organic solvent volatile content. Next, the obtained slurry was cooled to room temperature and filtered under reduced pressure. 200 parts of ion-exchanged water was added to the filter cake, and the mixture was mixed at 800 rpm for 5 minutes using a Three-One Motor (manufactured by Shinto Scientific Co., Ltd.) to reslurry, and then filtered. Furthermore, 10 parts of 1% by mass aqueous sodium hydroxide solution and 190 parts of ion-exchanged water were added to the filter cake, and the mixture was similarly reslurried, and then filtered. Next, 10 parts of 1% by mass hydrochloric acid and 190 parts of ion-exchanged water were added to the filter cake, and the mixture was similarly reslurried, and then filtered. Furthermore, the operation of adding 300 parts of ion-exchanged water to the filter cake, reslurrying, and then filtering was repeated twice. Using a circulating air dryer, the filtered cake was passed through a mesh with 2 mm openings, then dried at 45°C for 96 hours, and sieved using a mesh with 75 μm openings to obtain core-shell type toner base particles having a core made of crystalline polyester resin SB3 and a shell made of amorphous polyester resin SA3.

[0166] (Preparation of White Toner S9) 100 parts of amorphous polyester resin dispersion SA3, 120 parts of crystalline polyester resin dispersion SB3, 125 parts of wax dispersion, 12 parts of a master batch of an organically modified layered inorganic compound, 60 parts of titanium oxide, and 63 parts of ethyl acetate were mixed and mixed for 120 minutes at 6,000 rpm using a homomixer to obtain an oil phase 01 (solid content 50%). 180 parts of the aqueous phase was placed in a vessel equipped with a stirrer and a thermometer, and then kept at 20°C on a water bath. Next, 5 parts of modified prepolymer 1 were added to 111 parts of oil phase 01 kept at 20°C, and the mixture was poured into the aqueous phase. While keeping the temperature at 20°C, the mixture was mixed at 8,000 rpm for 2 minutes using a TK homomixer to obtain an emulsified slurry. The emulsified slurry was placed in a vessel equipped with a stirrer and a thermometer, and the solvent was removed under reduced pressure at 40°C to obtain a slurry with a solid content of 80% in the oil droplets. The obtained slurry was mixed at 8,000 rpm for 5 minutes using a TK homomixer while maintaining the temperature at 40°C. The slurry was subjected to shear stress and then desolvated under reduced pressure at 40°C to obtain a slurry with 0% organic solvent volatile content. Next, the obtained slurry was cooled to room temperature and filtered under reduced pressure. 200 parts of ion-exchanged water was added to the filter cake, and the mixture was mixed at 800 rpm for 5 minutes using a Three-One Motor (manufactured by Shinto Scientific Co., Ltd.) to reslurry, and then filtered. Furthermore, 10 parts of 1% by mass aqueous sodium hydroxide solution and 190 parts of ion-exchanged water were added to the filter cake, and the mixture was similarly reslurried, and then filtered. Next, 10 parts of 1% by mass hydrochloric acid and 190 parts of ion-exchanged water were added to the filter cake, and the mixture was similarly reslurried, and then filtered. Furthermore, the operation of adding 300 parts of ion-exchanged water to the filter cake, reslurrying, and then filtering was repeated twice. The filter cake was dried in a circulating air dryer at 45°C for 48 hours without crumbling, and then sieved using a mesh with 75 μm openings to obtain core-shell type toner base particles having a core made of crystalline polyester resin SB3 and a shell made of amorphous polyester resin SA3.

[0167] (Preparation of White Toner S10) White toner S10 was produced in the same manner as white toner S1, except that the classification time of the fine powder classifier (Faculty / Hosokawa Micron) was changed to 10 minutes so that the final average circularity would be 0.910.

[0168] (Preparation of White Toner S11) 100 parts of amorphous polyester resin dispersion SA4, 20 parts of crystalline polyester resin dispersion SB3, 25 parts of wax dispersion, 12 parts of a master batch of an organically modified layered inorganic compound, 60 parts of titanium oxide, and 63 parts of ethyl acetate were mixed and mixed for 120 minutes at 6,000 rpm using a homomixer to obtain an oil phase (solid content 50%). 174 parts of the aqueous phase was placed in a vessel equipped with a stirrer and a thermometer, and then kept at 20°C on a water bath. Next, 5 parts of modified prepolymer 1 were added to 111 parts of the oil phase kept at 20°C, and the mixture was poured into the aqueous phase. While keeping the temperature at 20°C, the mixture was mixed at 8,000 rpm for 2 minutes using a TK homomixer to obtain an emulsified slurry. The emulsified slurry was placed in a vessel equipped with a stirrer and a thermometer, and the solvent was removed under reduced pressure at 40°C to obtain a slurry with a solid content of 80% in the oil droplets. The obtained slurry was mixed at 8,000 rpm for 5 minutes using a TK homomixer while maintaining the temperature at 40°C. The slurry was subjected to shear stress and then desolvated under reduced pressure at 40°C to obtain a slurry with 0% organic solvent volatile content. Next, the obtained slurry was cooled to room temperature and filtered under reduced pressure. 200 parts of ion-exchanged water was added to the filter cake, and the mixture was mixed at 800 rpm for 5 minutes using a Three-One Motor (manufactured by Shinto Scientific Co., Ltd.) to reslurry, and then filtered. Furthermore, 10 parts of 1% by mass aqueous sodium hydroxide solution and 190 parts of ion-exchanged water were added to the filter cake, and the mixture was similarly reslurried, and then filtered. Next, 10 parts of 1% by mass hydrochloric acid and 190 parts of ion-exchanged water were added to the filter cake, and the mixture was similarly reslurried, and then filtered. Furthermore, the operation of adding 300 parts of ion-exchanged water to the filter cake, reslurrying, and then filtering was repeated twice. The filter cake was dried in a circulating air dryer at 45° C. for 48 hours without crumbling, and then sieved using a mesh with 75 μm openings to obtain core-shell type toner base particles having a crystalline polyester core and an amorphous polyester shell.

[0169] 2-2. Measurement of physical properties (viscosity) The viscosity of the white toner was measured using a flow tester (device name: CFT-500, manufactured by Shimadzu Corporation) under the following conditions and procedures. First, 1.1 g of white toner in a powder state was placed in a cylinder that had been kept at 50° C., and preheated for 300 seconds. Next, while being heated at a rate of 6°C / min, the white toner was pressurized with a plunger (applied a load of 2 kg), and the molten white toner was caused to flow out from a cylindrical die hole (hole inner diameter: 1.0 mm, die length: 1.0 mm) provided at the bottom of the cylinder. Data was measured until the dissolution was completely completed, and the viscosity value when it reached 110°C was read and logarithmically converted to calculate logμ(W110).

[0170] (Average circularity of toner particles) The toner particles of the white toner were wetted with a surfactant solution and dispersed by ultrasonic dispersion for 1 minute. The peripheral length of the projected image of each particle was measured using a flow type particle image analyzer "FPIA-3000" (manufactured by Sysmex Corporation) under the measurement condition of HPF (high magnification imaging) mode at an appropriate concentration of 3000 to 10000 HPF detections. The circularity of each particle was then calculated based on the following formula. Circularity = (perimeter of a circle with the same projected area as the particle image) / (perimeter of the projected particle image) The circularity of each particle was then added up and divided by the total number of particles measured to obtain an arithmetic mean value, which was taken as the average circularity.

[0171] (Volume-based median diameter (D50)) The volume-based median diameter (D50) was measured and calculated using, for example, a device such as "Multisizer 3 (Beckman Coulter)" connected to a computer system for data processing. First, 0.02 g of toner particles were mixed with 20 ml of a surfactant solution (a surfactant solution prepared by diluting, for example, a neutral detergent containing a surfactant component 10 times with pure water in order to disperse the toner particles), and then ultrasonic dispersion was performed for 1 minute to prepare a toner particle dispersion. This toner particle dispersion was pipetted into a beaker containing an ISOTON II (manufactured by Beckman Coulter) in a sample stand until the measurement concentration reached 5-10%, and the measurement was performed with the measurement count set to 25,000 particles. The aperture diameter of the Multisizer 3 used was 100 μm. The measurement range of 1-30 μm was divided into 256 parts, and the frequency count was calculated, and the particle diameter with the largest volume cumulative fraction of 50% was determined as the volume-based median diameter (D50).

[0172] Table 1 shows the resin compositions, production conditions, and physical properties of the white toners S1 to S11.

[0173] [Table 1]

[0174] 2-3. Preparation of color toner (Manufacturing color toner Y1 / M1 / C1 / B1) Amorphous polyester resin A1: 60 parts Crystalline polyester B1: 40 parts Diester wax: 5 parts (melting point: 95°C) Colorant: 12 parts As colorants, a yellow pigment (Pigment Yellow 74) was used to prepare the yellow toner, a magenta pigment (quinacridone) was used to prepare the magenta toner, a cyan pigment (phthalocyanine blue (CI Pigment Blue 15:3)) was used to prepare the cyan toner, and a black pigment (carbon black) was used to prepare the black toner. The above materials were mixed in a Henschel mixer at 40 m s -1 The mixture was mixed at a speed of 1000 rpm for a rotation time of 5 min. The mixture was then kneaded in a twin-screw kneader set at a temperature of 130°C. The kneaded mixture was cooled and coarsely crushed to 1 mm or less in a hammer mill to obtain a coarsely crushed product. The coarsely crushed product was finely crushed in a mechanical crusher. The finely crushed precursor was then classified using an air classifier to obtain particles with a volumetric median diameter of 6.4 μm. The classified particles were dried using an airflow dryer under the following operating conditions: hot air temperature: 130° C.; drying time: 30 minutes; color toner base particles were obtained.

[0175] Then, 1.0 parts by mass of hydrophobic silica particles A (number average primary particle size: 16 nm, hydrophobicity: 68) and 1.5 parts by mass of large-diameter silica particles B (number average primary particle size: 50 nm) were added to 100 parts by mass of color toner base particles, and mixed for 1 minute at a peripheral speed of 35 m / s using a Henschel mixer, paused, and then mixed for another 5 minutes. The mixture was sieved using a mesh with 43 μm openings to obtain color toner particles Y1 / M1 / C1 / B1.

[0176] (Manufacturing color toner Y2 / M2 / C2 / B2~Y5 / M5 / C5 / B5) Color toners Y2 / M2 / C2 / B2 to Y5 / M5 / C5 / B5 were prepared in the same manner as color toner Y1 / M1 / C1 / B1, except that the contents of amorphous polyester resin and crystalline polyester resin in color toner Y1 / M1 / C1 / B1 were changed as shown in Table 2.

[0177] (Preparation of color toner Y6 / M6 / C6 / B6, Y8 / M8 / C8 / B8, Y10 / M10 / C10 / B10) Color toners Y6 / M6 / C6 / B6 were produced in the same manner as color toners Y1 / M1 / C1 / B1, except that the drying conditions were changed as shown in Table 2 in the preparation of color toners Y1 / M1 / C1 / B1.

[0178] (Preparation of color toner Y7 / M7 / C7 / B7) Color toners Y7 / M7 / C7 / B7 were prepared in the same manner as color toners Y1 / M1 / C1 / B1, except that the types of amorphous polyester resin and crystalline polyester resin were changed as shown in Table 2 in the preparation of color toners Y1 / M1 / C1 / B1.

[0179] (Preparation of color toner Y9 / M9 / C9 / B9) -Preparation of yellow pigment masterbatch- 200 parts of water, 500 parts of CI Pigment Yellow 185 (Paliotol Yellow D1155, manufactured by BASF), and 500 parts of amorphous polyester resin L1 were added and mixed in a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.). The mixture was kneaded using two rolls at 120°C for 30 minutes, then rolled and cooled, and pulverized using a pulverizer to obtain [Yellow Pigment Masterbatch 1]. The same procedure was followed for the other colors, and the color materials were as described above.

[0180] -Synthesis of wax dispersant 1- In a reaction vessel equipped with a stirring rod and a thermometer, 480 parts of xylene and 100 parts of paraffin wax HNP-9 (manufactured by Nippon Seiro Co., Ltd.) were placed and heated until dissolved, and then the atmosphere was replaced with nitrogen and the temperature was raised to 170° C. Next, 740 parts of styrene, 100 parts of acrylonitrile, 60 parts of butyl acrylate, 36 parts of di-t-butylperoxyhexahydroterephthalate, and A mixture of 100 parts of xylene was added dropwise over 3 hours, and then the mixture was kept at 170° C. for 30 minutes. The solvent was then removed to obtain Wax Dispersant 1.

[0181] -Preparation of masterbatch 1 of organically modified layered inorganic compound- 200 parts of water, 500 parts of organically modified layered inorganic compound (CLAYTONE APA, manufactured by BYK Japan Co., Ltd.), and 500 parts of amorphous polyester resin L1 were added and mixed in a Henschel mixer (manufactured by Nippon Coke & Engineering Co., Ltd.). The mixture was kneaded for 30 minutes at 120°C using two rolls, rolled and cooled, and pulverized in a pulverizer to obtain [Master batch 1 of organically modified layered inorganic compound]. Based on the above, a color toner was manufactured.

[0182] 100 parts of amorphous polyester resin dispersion A3, 20 parts of crystalline polyester resin dispersion B3, 25 parts of wax dispersion W1, 2 parts of master batch 1 of an organically modified layered inorganic compound, 12 parts of a master batch of a yellow pigment, and 69 parts of ethyl acetate were mixed and mixed for 120 minutes at 6,000 rpm using a TK homomixer (manufactured by Primix Corporation) to obtain an oil phase Y1 (solid content 50%).

[0183] 160.5 parts of the aqueous phase was placed in a vessel equipped with a stirrer and a thermometer, and then kept at 20°C on a water bath. Next, 5 parts of modified prepolymer 1 were added to 102 parts of oil phase Y1 kept at 20°C, and the mixture was poured into the aqueous phase. While keeping the temperature at 20°C, the mixture was mixed at 8,000 rpm for 2 minutes using a TK homomixer (manufactured by Primix Corporation) to obtain an emulsified slurry. The solvent was removed under reduced pressure at 0° C. to obtain a slurry with an organic solvent volatile content of 0%. Next, the obtained slurry was cooled to room temperature and filtered under reduced pressure. 200 parts of ion-exchanged water was added to the filter cake, and the mixture was mixed at 800 rpm for 5 minutes using a Three-One Motor (manufactured by Shinto Scientific Co., Ltd.) to reslurry, and then filtered. Furthermore, 10 parts of 1% by mass aqueous sodium hydroxide solution and 190 parts of ion-exchanged water were added to the filter cake, and the mixture was similarly reslurried, and then filtered. Next, 10 parts of 1% by mass hydrochloric acid and 190 parts of ion-exchanged water were added to the filter cake, and the mixture was similarly reslurried, and then filtered. Furthermore, the operation of adding 300 parts of ion-exchanged water to the filter cake, reslurrying, and then filtering was repeated twice.

[0184] Using a circulating air dryer, the filtered cake was passed through a mesh with 2 mm openings, then dried at 45°C for 96 hours, and sieved using a mesh with 75 μm openings to obtain core-shell type toner base particles with a core made of crystalline polyester resin and a shell made of amorphous polyester resin.

[0185] (Preparation of Color Toner Y11 / M11 / C11 / B11) 100 parts of amorphous polyester resin dispersion A3, 20 parts of crystalline polyester resin dispersion B3, 25 parts of wax dispersion W1, 2 parts of organically modified layered inorganic compound master batch 1, 12 parts of yellow pigment master batch 1, and 69 parts of ethyl acetate were mixed and mixed for 120 minutes at 6,000 rpm using a TK homomixer (manufactured by Primix Corporation) to obtain oil phase Y1 (solid content 50%).

[0186] 160.5 parts of the aqueous phase was placed in a vessel equipped with a stirrer and a thermometer, and then the mixture was kept at 20°C on a water bath. Next, 5 parts of modified prepolymer 1 were added to 102 parts of oil phase Y1 kept at 20°C, and the mixture was poured into the aqueous phase. While keeping the temperature at 20°C, the mixture was mixed at 8,000 rpm for 2 minutes using a TK homomixer (manufactured by Primix Corporation) to obtain an emulsified slurry. The solvent was removed under reduced pressure at 40°C to obtain a slurry with an organic solvent volatile content of 0%. The obtained slurry was then cooled to room temperature and filtered under reduced pressure. 200 parts of ion-exchanged water was added to the filter cake, and the mixture was mixed at 800 rpm for 5 minutes using a Three-One Motor (manufactured by Shinto Scientific Co., Ltd.) to reslurry, and then filtered. Furthermore, 10 parts of 1% by mass aqueous sodium hydroxide solution and 190 parts of ion-exchanged water were added to the filter cake, and the mixture was similarly reslurried, and then filtered. Next, 10 parts of 1% by mass hydrochloric acid and 190 parts of ion-exchanged water were added to the filter cake, and the mixture was similarly reslurried, and then filtered. Furthermore, the operation of adding 300 parts of ion-exchanged water to the filter cake, reslurrying, and then filtering was repeated twice. The filter cake was dried in a circulating air dryer at 45°C for 48 hours without being crumbled, and then sieved using a mesh with 75 μm openings to obtain core-shell type toner base particles having a core made of crystalline polyester resin and a shell made of amorphous polyester resin.

[0187] 2-4. Measurement of physical properties (viscosity) In the above-mentioned viscosity measurement method, data was measured until the dissolution was completely completed, and the viscosity value when 100°C was reached was read, and logμ(C100) was calculated in the same manner.

[0188] (average circularity, median diameter) The average circularity and median diameter were measured in the same manner as described above.

[0189] Table 2 shows the resin compositions, production conditions, and physical properties of color toners 1 to 13.

[0190] [Table 2]

[0191] 3. Testing and Evaluation <Tests 1-19> As the image forming apparatus, a commercially available electrophotographic printer "magicolor (registered trademark) 2300DL" (manufactured by Konica Minolta, Inc.) in which the fixing unit was modified to the SURF fixing unit shown in FIG. 3 was used. The following tests were performed under the conditions shown in Table 3 using the white toner and color toners shown in the same table. In each test, the fixing temperature refers to the set temperature of the fixing belt (heater temperature), and the surface temperature of the pressure roller 63 facing the fixing belt was always set to a temperature 50°C lower than that of the fixing belt. In Test 18, an unmodified product in which the fixing unit was a roller fixing device was used.

[0192] The recording media used are as follows: PET film: PET50A (Lintec Corporation, A4 80g·m 2 ) PP film: PP top clear BO (Avery Dennison Corporation, roll paper, 112 m 2 ) Paper: npi wood-free paper (Nippon Paper Industries Co., Ltd., roll paper, 127.9 g m 2 )

[0193] 3-1. Image surface roughness First, white toner and color toner were layered in this order on the recording medium to form a solid chart with a printing rate of 20%. The toner adhesion amount was 8 g / m 2, color toner 4g / m 2 It was decided. Next, the solid chart was set to white + color overlay and 10,000 sheets were output at a fixing temperature of 150°C. When roll paper was used, an image equivalent to 10,000 sheets was output. When it was not possible to set the roll in the paper feed mechanism, the roll paper was cut to A4 size and an image output test of 10,000 sheets was performed. Then, for the 9,000th to 10,000th images output, the surfaces of the toner images were visually observed under an optical microscope and evaluated according to the following criteria. ◎: No problem ○: Some unevenness and scratches can be seen △: Unevenness and scratches can be seen ×: Streaks are clearly present

[0194] 3-2.Belt breakability A solid chart equivalent to a printing rate of 20% was formed in the same manner as in 3-1 above, and 10,000 sheets were output at a fixing temperature of 150°C. When roll paper was used, an image was output at a length equivalent to 10,000 sheets. When the roll could not be set in the paper feed mechanism, the roll paper was cut to A4 size and an image output test of 10,000 sheets was performed. If the fixing belt broke, cracked, folded, etc. during this test, the test was stopped, and if there were no problems, it was output to the end. The belt breakability was evaluated according to the following criteria. ◎: 10,000 sheets passed through without breaking ○: When observing the belt surface, small scratches are visible, but there are no breaks. △: When observing the belt surface, there are visible small scratches, but the belt is not broken. ×: The belt breaks during the evaluation.

[0195] 3-3.Low temperature fixability A solid chart was formed by layering the white toner and the color toner in this order on the recording medium. The toner adhesion amount was 8 g / m 2 , color toner 4g / m 2 It was decided. Next, a test was conducted in which the printout was performed at a fixing temperature of 175°C and a fixing speed of 250 mm / sec, while decreasing the fixing temperature in increments of 5°C, until cold offset occurred (an image defect in which the toner image peels off the paper and some parts of the paper surface are visible due to insufficient melting of a solid toner image by the heat given when passing through the fixing section). The fixing temperature setting value at which cold offset did not occur was recorded, and this was used as the minimum fixing temperature to evaluate low-temperature fixability. ◎: Minimum fixing temperature is 130℃ or less ○: Minimum fixing temperature is over 130℃ and 150℃ or less △: Minimum fixing temperature is over 150℃ and below 170℃ ×: The minimum fixing temperature is over 170°C The lower the minimum fixing temperature, the better the low-temperature fixing property.

[0196] 3-4. Image Blister A solid chart equivalent to a printing rate of 20% was printed on the recording medium with white + color overlapping settings, and 30 sheets were output at a fixing temperature of 150°C. When roll paper was used, an image equivalent to 30 sheets was output. When the roll could not be set in the paper feed mechanism, the roll paper was cut to A4 size and an image output test of 10,000 sheets was performed. The surface of the toner image for all output images was then visually observed using an optical microscope and evaluated according to the following criteria. ◎: No problem ○: Blisters occur in 1 to 2 places within the specified area △: Blisters occur in 3 to 4 places within the specified area, but there is no problem in practical use. ×: Four or more blisters occurred within a given area / image output was not possible and evaluation was not possible The image blister refers to a state in which, when the toner is melted by fixing, moisture contained in the air layer present in the white toner layer as a base evaporates, causing the surface of the toner layer to become rough with air bubbles.

[0197] The evaluation results of tests 1 to 19 are shown in Table 3.

[0198] [Table 3]

[0199] As shown in Table 3, in tests 17 and 19, where the logarithmic viscosity difference Δ(lоgμW(110)-lоgμC(100)) between the white toner and the color toner is less than 0.3, image surface roughness and belt breakage occur. In test 18, which uses roller fixing, low-temperature fixing ability is poor.

[0200] In contrast, in tests 1 to 16 where the logarithmic viscosity difference Δ between the white toner and the color toners is 0.3 or more, it is found that fixing can be achieved at a low temperature by surf fixing, and image surface roughness and belt breakage can also be reduced.

[0201] From these findings, it can be seen that by setting the logarithmic viscosity difference Δ between the white toner and the color toners to 0.3 or more and fixing by surf fixing, it is possible to obtain low-temperature fixability while reducing image surface roughness and belt breakage.

[0202] In particular, it is understood that by setting the logarithmic value difference Δ to 0.5 or more, image surface roughness can be further reduced (Comparison between Tests 4 and 5).

[0203] Also, it is understood that image blisters can be further suppressed by appropriately lowering the logarithmic value of the viscosity of the white toner (Comparison of Tests 1, 6, and 7).

[0204] It is also clear that image surface roughness and belt breakage can be reduced by lowering the average circularity (comparison between Tests 1 and 16). [Industrial Applicability]

[0205] According to the present invention, it is possible to provide an image forming method and an image forming apparatus capable of forming an image having excellent low-temperature fixing property and having little surface roughness. [Explanation of symbols]

[0206] 1. Image forming device 10 Heating belt 30 Image processing section 40 Image forming section 41Y, 41M, 41C, 41K Image forming unit 42 Intermediate transfer unit 43 Secondary transfer unit 50 Conveyor 51 Paper feed section 51a, 51b, 51c Paper feed tray unit 52 Paper output section 52a Paper ejection roller 53 Conveying path section 53a Registration roller pair 60 Fixing unit 61 Fixing belt 62 Heater 63 Pressure Roller 70 Image reading unit 71 Paper feeder 72 Scanner 72a CCD sensor 100 Surface treatment device 110 Hopper 120 Mixing room 130 Nozzle 140 Dispersed Airflow 150 Diffuser 160 Heat Treatment Room 170 Hot air swirling chamber 180 Cold air supply section 190 Discharge section 200 Surface treatment equipment 210 Heat Treatment Room 220 Introductory tube 222 Protruding members 230 Supply pipe 240 Powder particle supply port 250 Hot air supply means 260 Hot air inlet 270 Swivel member 280 Distribution member 290 Cold air introduction section 411 Exposure equipment 412 Developing device 413 Electrophotographic photoreceptor 414 Charging device 415 Drum cleaning device 421 Intermediate transfer belt 422 Primary transfer roller 423, 431 Support roller 423A Backup roller 426 Belt cleaning device 426a Elastic members 431A Secondary transfer roller 432 Secondary transfer belt D Manuscript S Recording medium

Claims

1. 1. An image forming method comprising: forming a toner image on a recording medium, the toner image including a white toner image and a color toner image disposed on the white toner image; fixing the toner image onto the recording medium; having In the fixing step, a recording medium on which the toner image is formed is nipped between a circular belt, at least a portion of the inner circumference of which is supported by a heating member, and an opposing member which faces the heating member and the circular belt via the circular belt, thereby fixing the toner image onto the recording medium under heat; the white toner constituting the white toner image and the color toners constituting the color toner images satisfy the following formula: Image forming method. 0.3≦logμ(W110)−logμ(C100) (logμ(W110) is the logarithm of the viscosity of the white toner at 110° C., logμ(C100) is the logarithm of the viscosity of the color toner at 100° C.

2. In the fixing step, the toner image is heated at a temperature of 130° C. or more and 170° C. or less. The image forming method according to claim 1 .

3. logμ(W110) is equal to or greater than 3.9 and equal to or less than 5.5; The image forming method according to claim 1 .

4. The white toner and the color toner satisfy the following formula: The image forming method according to claim 1 . 0.5≦logμ(W110)−logμ(C100)≦1.5

5. The white toner includes white toner base particles, The average circularity of the white toner base particles is 0.920 or more and 0.955 or less. The image forming method according to claim 1 .

6. The color toner includes color toner base particles, the average circularity of the color toner base particles is 0.920 or more and 0.955 or less; The image forming method according to claim 5 .

7. the moisture content of the white toner and the color toner is 0.1% or more and 0.6% or less, The image forming method according to claim 1 .

8. An image forming apparatus, a fixing unit that fixes a toner image including a white toner image and a color toner image disposed on the white toner image onto a recording medium; The fixing unit is A circular belt; A heating member disposed on an inner peripheral surface side of the circular belt; an opposing member disposed on an outer peripheral surface side of the circular belt so as to face the heating member with the circular belt interposed therebetween; having the fixing unit nips the recording medium on which the toner image is formed between the circular belt supported by the heating member and the opposing member, and fixes the toner image onto the recording medium; The white toner and the color toner satisfy the following formula: Image forming device. 0.3≦logμ(W110)−logμ(C100) (logμ(W110) is the logarithm of the viscosity of the white toner at 110° C., logμ(C100) is the logarithm of the viscosity of the color toner at 100° C.

Citation Information

Patent Citations

  • Image forming method and image forming apparatus

    JP2021162839A

  • Powdered medicine weighing device

    JP2022048310A